Suppressive effect of epigallocatechin‐3‐O‐gallate on endoglin molecular regulation in myocardial fibrosis in vitro and in vivo. Issue 11 (16th June 2016) - Lin, Chiu‐Mei; Chang, Hang; Wang, Bao‐Wei; Shyu, Kou‐Gi
Abstract: Epigallocatechin‐3‐O‐gallate (EGCG), derived from green tea, has been studied extensively because of its diverse physiological and pharmacological properties. This study evaluates the protective effect of EGCG on angiotensin II (Ang II)‐induced endoglin expression in vitro and in vivo . Cardiac fibroblasts (CFs) from the thoracic aorta of adult Wistar rats were cultured and induced with Ang II. Western blotting, Northern blotting, real‐time PCR and promoter activity assay were performed. Ang II increased endoglin expression significantly as compared with control cells. The specific extracellular signal‐regulated kinase inhibitor SP600125 (JNK inhibitor), EGCG (100 μM) and c‐Jun N‐terminal kinase (JNK) siRNA attenuated endoglin proteins following Ang II induction. In addition, pre‐treated Ang II‐induced endoglin with EGCG diminished the binding activity of AP‐1 by electrophoretic mobility shift assay. Moreover, the luciferase assay results revealed that EGCG suppressed the endoglin promoter activity in Ang II‐induced CFs by AP‐1 binding. Finally, EGCG and the JNK inhibitor (SP600125) were found to have attenuated endoglin expression significantly in Ang II‐induced CFs, as determined through confocal microscopy. Following in vivo acute myocardial infarction (AMI)‐related myocardial fibrosis study, as well as immunohistochemical and confocal analyses, after treatment with endoglin siRNA and EGCG (50 mg/kg), the area of myocardial fibrosis reduced by 53.4% and 64.5% and attenuated the left ventricular end‐diastolic and systolic dimensions, and friction shortening in hemodynamic monitor. In conclusion, epigallocatechin‐3‐O‐gallate (EGCG) attenuated the endoglin expression and myocardial fibrosis by anti‐inflammatory effect in vitro and in vivo, the novel suppressive effect was mediated through JNK/AP‐1 pathway.